FORMULASI DAN UJI AKTIVITAS GEL ANTIJERAWAT FRAKSI N-HEKSAN DAUN KERSEN (Muntingia calaburaL.) TERHADAP BAKTERI Propionibacterium acnes - Saparuddin Latu; Musnur, Aldha Irjayanti; Jangga, Jangga; Mansur, Mansur (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
ABSTRACT Cherry leaves contain many compounds, namely flavonoids, tannins, saponins, phenolics, steroids, and alkaloids. One of the compounds that act as an antibacterial is the flavonoid compound. One of the uses of cherry leaves is anti-acne. Acne is a chronic inflammatory disease of the pilosebaceous glands. One of the bacteria that causes acne is Propionibacterium acnes bacteria. Preparations that can be made for anti-acne are gel preparations. This study aims to determine whether the n-hexane fraction of cherry leaf (Muntingia calabura L.) can be made into anti-acne gel preparations and to find out at what concentration the n-hexane fraction of cherry leaf (Muntingia calabura L.) in anti-acne gel preparations can provide antioxidant activity. inhibiting the growth of Propionibacterium acnes bacteria. This research method is true experimental by making an anti-acne gel preparation of the n-hexane fraction of cherry leaves (Muntingia calabura L.) with various concentrations of 2.5%, 5%, 7.5% and testing the activity of the preparation against Propionibacterium acnes using the well method. so that. The results of the gel preparation formula showed that there were significant differences before and after the cycling test in both organoleptic, homogeneity, pH, viscosity, spreadability and adhesion tests. The activity test results obtained were that the largest inhibition zone was the concentration of 2.5%, namely 11.7 mm, which was in the strong category, while the 5% concentration, which was 13.4 mm, was in the strong category, and the concentration of 7.5%, which was 15.0 mm, was included in the category strong.